Ontogenetic development of physical efficiency in the age from 3 to 80 years against the background of the development of body structure traits - Pawłowska, Elżbieta (Anthropological Review, 1984)
Physical efficiency is a proof of the maturity degree and efficiency of the organism demonstrated primarily in physical efforts. The evaluation of the physical development according to the morphological criterion is based on the measurements of different traits of body structure. Statistical analysis of morphological traits has shown that the trend of ontogenetic development of these traits agrees with the course of the logistic curve. The maximum growth rate of the studied morphological traits (puberty leap) is reached earlier by women which is connected with their shorter growing period. Among the motoric traits studied in this work, the logistic curve can be adapted only for the development of the grip of finger flexors, changes in the remaining traits referring to other aspects of motorics in the human ontogenesis are more complicated and cannot be easily described with the help of one function for the total development. In the development of the abdominal muscle force in women and in men, the following periods can be distinguished: the childhood period lasting until about the 12th year of age chąracterized by a drop in the value of this trait for children. of both sexes. After the age of 12 years, in girls - the force of abdominal muscles is slightly better and it is maintained at this. level until an old age, whereas in boys after the age of 12 years the value of this trait increases, and about the age of 25 years men reach a second maximum of force (the first maximum is characteristic for the pre-school age). This high value of the force of abdominal muscles in men is maintained until about the 45th year of age, then it distinctly falls down. In the ontogenetic development of the speed measured by the, time of executing 10 knee bendings, three periods can be distinguished in women and in men. In the pre-school age there occurs a shortening of the time for executing 10 knee bendings, the shortest time is reached in the age of about 11-12 years for both sexes (the rate of progressive development of this trait is higher in girls). In the further stages of ontogenesis the time of executing 10 knee bendings becomes longer. The speed measured by the time of simple reaction is negatively correlated with age in girls and boys until the 14th year of age, i.e. it is getting shorter with the development.The resistance measure in this work are the changes in the rest and effort heartbeates rates. The dependence of rest heart rate frequency on the age. has a linear character, the trend of the regrssion line is negative. After physical effort the frequency of heart contraction increases. Until the 10th year of age effort heart rate inéreases (faster in girls), whereas after the 10th year of. age the dependence of effort heart rate on age is also linear but negative. Flexibility as a motoric trait is strongly age related. The average values of this trait in women in all periods of ontogenesis are positive, whereas in boys in the age of 8-13 years the flexibility is negative. Women reach their greatest flexibility in the age of about 25 years, and in men this takes place as late as about the 35th year of age. After 35 years of age in men there occurs a considerable drop of flexibility, whereas in women it only slightly diminishes. The last trait of motoric activity analysed in this work is the force. The progressive development of force is characterized by an equal increasing rate for both sexes, whereas in women it lasts until about the 15th year of age, and in men until about the 20th year of age, then there follows a drop in the value of the trait, its speed being faster in women.The development of motoric traits shows a differentiation of the trend in the period of the whole life of an individual traits closer related with the homeostasis of the human organism show smaller changes than specific traits of unilateral physical efficiency (e.g. long jump). When motoric traits are the subject of studies, the classical division into three stages: growth, stabilization, and involution cannot be maintained since the peak of physical efficiency for different traits falls in different age periods (developmental allometry).